Mary had a little plan - Sauer, Tammi (Mary had a little glam, 2022)
"Fashion-forward Mary is known for adding flair everywhere she goes. When she spots an abandoned lot in her neighborhood, Mary knows she can use her stylish talent to spruce it up. Soon she's rallying neighborhood shops and calling on her friends to help. With Mary leading the way, this group carries out her little plan that has a big impact on her community!" --